Implementation of Meeting Minutes, Neofeeder and SISTER at STT Humble and STT Berea - Azriel Christian Nurcahyo; Fitria Elvi; Rifqi Hammad (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2022)
High Schools of Technology or abbreviated as STT Humble and STT Berea, are two institutions that are under the Director General of Christian Guidance in monitoring and reporting but must be integrated with the Ministry of Education and Culture through a Neofeeder. So far, the existence of STT Humble in Bengkayang Regency and STT Berea in Ansang, Darit, Landak Regency has become the prima donna for undergraduate higher education for prospective Christian teachers and prospective ministers such as missionaries and pastors. However, in practice, the limitations of information technology-based services in both STTs make it very difficult to see the unavailability of IT personnel. For example, the need to coordinate with each other is not documented in meeting minutes until the existence of the Pddikti feeder application, which has turned into a Neofeeder through monthly updates and a SISTER service for BKD services for each lecturer. Through this community service, the implementation of digital-based meeting minutes for STT Humble, and an online cloud for neo feeder, to the management of VMware-based SISTERs for STT Berea were designed.